1999
DOI: 10.1108/07363769910297498
|View full text |Cite
|
Sign up to set email alerts
|

Smokers and beer drinkers: values and consumer susceptibility to interpersonal influence

Abstract: Examines the personal values of college‐age smokers and beer drinkers, as well as their susceptibility to interpersonal influence. Findings suggest that, compared to non‐smokers, smokers are less likely to place importance on the values of security, being well respected, and having a sense of belonging. When compared to non‐beer drinkers, college students who are beer drinkers are more likely to place importance on the value of excitement, and are less likely to place importance on the value of security. Smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 80 publications
1
30
0
3
Order By: Relevance
“…Batra et al 2001). Consumers' importance of social values is positively related to SNI (Batra et al 2001;Kropp et al 1999). On the basis of these arguments, we expect consumers with stronger social needs to be more susceptible to informational and normative interpersonal influences when they invest than are consumers who have less explicit social needs.…”
Section: Hypothesesmentioning
confidence: 92%
See 1 more Smart Citation
“…Batra et al 2001). Consumers' importance of social values is positively related to SNI (Batra et al 2001;Kropp et al 1999). On the basis of these arguments, we expect consumers with stronger social needs to be more susceptible to informational and normative interpersonal influences when they invest than are consumers who have less explicit social needs.…”
Section: Hypothesesmentioning
confidence: 92%
“…The important effects of consumers' susceptibility to interpersonal influence (CSII) on their decision-making processes have been documented extensively in consumer behavior and marketing literature (Bearden et al 1989Bristol and Mangleburg 2005;Kropp et al 1999;Mascarenhas and Higby 1993;Mourali et al 2005;Ratner and Kahn 2002). However, none of these studies address consumers' investment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Although research on susceptibility to interpersonal influence has focused primarily on purchase behaviours, social issues (Kropp et al, 1999) and environmental behaviour (Pickett et al, 1993), it has not been explored within the realms of donation behaviour. However, this may well be an oversight, particularly in relation to conspicuous donation behaviour.…”
Section: Susceptibility To Interpersonal Influencementioning
confidence: 99%
“…Kropp et al (1999) reported that college students who consumed beer were more likely than non-beer consumers to report high Stimulation and low Security values.…”
Section: Introductionmentioning
confidence: 99%